Renal Impairment after Spontaneous Bacterial Peritonitis: Incidence and Prognosis - Gabriela Perdomo Coral; Angelo Alves de Mattos (Canadian Journal of Gastroenterology)
BACKGROUND/AIMS: Spontaneous bacterial peritonitis (SBP) is an important complication in cirrhotic patients. The aim of the present study was to assess the incidence, predictive factors and prognosis for renal impairment (RI) after SBP in cirrhotic patients from southern Brazil.